Targeting thymidine phosphorylase alleviates resistance to dendritic cell immunotherapy in colorectal cancer and promotes antitumor immunity - Paladhi, Ankush; Daripa, Samrat; Mondal, Indrani; Hira, Sumit Kumar (Frontiers in Immunology, 2022)
T-cell exhaustion plays a pivotal role in the resistance of microsatellite-stable colorectal cancer (CRC) to immunotherapy. Identifying and targeting T-cell exhaustion-activating mechanisms is a promising strategy to augment the effects of immunotherapy. Here, we found that thymidine phosphorylase (TYMP) plays a decisive role in inducing systemic T-cell exhaustion and abrogating the efficacy of dendritic cell (DC) therapy in a CRC model. Targeting TYMP with tipiracil hydrochloride (TPI) induces immunological cell death (ICD). The combined effects of TPI and imiquimod-activated DCs turn CT26 tumors into immunologically ‘hot’ tumors by inducing ICD in vivo. High-dimensional cytometry analysis revealed T-cell and IFN-γ dependency on the therapeutic outcome. In addition, chemoimmunotherapy converts intratumoral Treg cells into Th1 effector cells and eliminates tumor-associated macrophages, resulting in higher cytotoxic T lymphocyte infiltration and activation. This effect is also associated with the downregulation of PD-L1 expression in tumors, leading to the prevention of T-cell exhaustion. Thus, cooperative and cognitive interactions between dendritic cells and immunogenic cell death induced by therapy with TPI promote the immune response and tumoricidal activities against microsatellite stable colorectal cancer. Our results support TYMP targeting to improve the effects of DC immunotherapy and outcomes in CRC.